Antiproliferative effects and molecular mechanisms of troglitazone in human cervical cancer in vitro - Ye, Jinjun (Onco Targets Ther, 2015)
We investigated the effects of troglitazone on human cervical cancer SiHa cells and its mechanisms of action. SiHa cells were incubated with different concentrations of troglitazone (100, 200, or 400 μg/mL) for 24, 48, and 72 hours. Cell viability was measured by 3-(4,5-dimethylthiazol-2-yl) 2,5-diphenyltetrazolium bromide (MTT) assay; cell cycle and apoptosis were detected by flow cytometry; and morphology of SiHa cells was observed under an inverted microscope. pcDNA3.1 and pcDNA3.1-Skp2 plasmids were constructed and then transfected into SiHa cells. Protein expression was analyzed by Western blotting. Troglitazone inhibited the proliferation of SiHa cells in a time- and concentration-dependent manner. Troglitazone caused G0/1 phase arrest but failed to reduce apoptosis in SiHa cells. Troglitazone significantly increased expression of p27 but decreased Skp2 expression. Skp2 overexpression inhibited the role of troglitazone in increasing expression of p27, and the cell cycle inhibitory effect of troglitazone. Troglitazone can inhibit SiHa cell viability by affecting cell cycle distribution but not apoptosis, and Skp2 and p27 may play a critical role.